Designing play-based learning chemistry activities in the preschool environment. Issue 3 (26th April 2019) - Adbo, Karina; Vidal Carulla, Clara
Abstract : This study focuses on the design of play-based learning activities for chemistry in preschool. Viewing chemistry as a part of our past and present culture instead of as a subject, provides the backdrop for a more holistic approach to chemistry within this specific environment. A cultural-historical perspective, together with scaffolding, emergent science skills and sustained shared thinking, made up the framework for the design of the learning activities. Results show that when scaffolding and emergent science skills are used within the design, they provide good support for both the content and the teacher in the actual learning situation. Working with scaffolding was also beneficial for professional development. However, for a progressive and inclusive activity design, it is essential to take into account aspects of the immediate environment and methods for direct evaluation.